2010
DOI: 10.1073/pnas.0911325107
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 regulates Dishevelled proteins and promotes transient and constitutive Wnt signaling

Abstract: Sirtuin 1 (SIRT1) is a class III histone deacetylase that deacetylates histone and nonhistone proteins to regulate gene transcription and protein function. Because SIRT1 regulates very diverse responses such as apoptosis, insulin sensitivity, autophagy, differentiation, and stem cell pluripotency, it has been a challenge to reconcile how it orchestrates such pleiotropic effects. Here we show that SIRT1 serves as an important regulator of Wnt signaling. We demonstrate that SIRT1 loss of function leads to a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 53 publications
4
98
1
Order By: Relevance
“…However, the expression of Sost was unaffected in the mice of the present work, suggesting that Sost could not be responsible for the bone phenotype. In other cell types, Sirt1 can stimulate Wnt signaling via regulating Dishevelled proteins (39) and by promoting epigenetic silencing of Wnt antagonists (40). It remains unknown whether these alternative mechanisms of Wnt signaling potentiation by Sirt1 play a role in osteoprogenitors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the expression of Sost was unaffected in the mice of the present work, suggesting that Sost could not be responsible for the bone phenotype. In other cell types, Sirt1 can stimulate Wnt signaling via regulating Dishevelled proteins (39) and by promoting epigenetic silencing of Wnt antagonists (40). It remains unknown whether these alternative mechanisms of Wnt signaling potentiation by Sirt1 play a role in osteoprogenitors.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, SIRT1 activation downregulated SIPS through FOXO3/p21 pathway, thereby protecting against emphysema. In addition to FOXO3, recent studies have demonstrated the involvement of other developmental and senescence-related genes, such as Wnt/β-catenin, Notch, Klotho, senescence marker protein-30, and Werner syndrome protein, in the development of emphysema (55)(56)(57)(58)(59)(60). However, it remains to be seen whether SIRT1 targets these genes in response to CS exposure.…”
Section: Discussionmentioning
confidence: 99%
“…7 Aberrant expression of WNT activates its signaling through autocrine mechanisms in colorectal sarcomas and sarcoma cell lines. [30][31][32] To examine the involvement of ATG4B-mediated autophagy on WNT signaling and tumor proliferation, we used human colorectal cancer HCT116 cells, a WNT3A expressed and a CTNNB1/β-catenin (catenin [cadherin-associated protein], β 1, 88 kDa)-mutated cell line that is highly responsive to WNT signaling. 31,33 Besides degradation of SQSTM1, protein levels of both DVL2 and CCND1 were decreased in colorectal cancer HCT116 cells silenced with ATG4B siRNA, and mRNA level of CCND1 was reduced in the ATG4B-knockdown cells (Fig.…”
Section: Atg4b Promotes Tumor Growth In Colorectal Cancer Cellsmentioning
confidence: 99%